Social engagement in coastal adaptation processes: Development and validation of the CoastADAPT scale. Issue 133 (July 2022) - Areia, Neide P.; Costa, Pedro J.M.; Tavares, Alexandre O.
Abstract: Introduction: Engaging citizens and communities is considered a central element and a good practice in coastal management. However, individuals still demonstrate a general disengagement with coastal risks. To understand the factors that underlie the citizens' engagement in coastal risks processes and to implement evidence-based strategies aimed at enhancing public participation in coastal management, is pivotal to the success of coastal adaptation. Goals: Therefore, this study sought to develop and validate an assessment tool aiming at measuring individuals' engagement in coastal adaptation processes and their underlying factors. Methods: A cross-sectional and 2-phase research was implemented to analyze the psychometric properties of the CoastADAPT scale. The Phase 1 study ( N = 491) determined the CoastADAPT scale's factorial structure, through Exploratory Factor Analysis; its reliability, through internal consistency and test-retest reliability; and construct validity, through convergent and divergent validity. The Phase 2 study ( N = 207) confirmed the CoastADAPT scale's factorial structure, through Confirmatory Factor Analysis. Results: Analyses indicated that the CoastADAPT scale showed good psychometric properties and a 3-factor structure consisting of the following domains: Experiential Processing (Affective component), Risk Awareness (Cognitive component) and Environmental Justice (Social value orientation component). Conclusions: The CoastADAPT scale is a reliable and valid measure of citizens' engagement in coastal risk adaptation processes. It may be a useful tool to facilitate the development of strategies to overcome individuals' disengagement with coastal management and to provide a deeper understanding of the predictors of individuals' engagement in coastal risk processes. Highlights: Citizens demonstrate a general disengagement with coastal risks. The CoastADAPT scale is a reliable measure of citizens' engagement in coastal risks. Affective, cognitive and social values factors explain the engagement in coastal risk.